COMPENSATION OF VOLUMETRIC EFFICIENCY BY TURBOCHARGING IN AN INSULATED DI DIESEL ENGINEWITH ALCOHOL AS FUEL - S.Sunil Kumar Reddy; V. Pandurangadu (European Scientific Journal, ESJ, 2013)
With the stringent emission legislation all over the world an intensive search is going on for diesel fuels which produce more environmental pollution. This simulated interest in alcohol-fueled diesel engines because it is renewable bio-based resource and it is oxygenated, thereby providing the potential to reduce particulate emissions in diesel engines and ethanol diffusion flames produce virtually no soot. But due to alcohols higher latent heat of vaporization, the higher temperatures available in the Insulated engine (IE) are used for vaporizing the alcohols and this decreases the ignition delay and aids combustion. With the higher temperatures in the insulated engines there will be drop in volumetric efficiency and this further increases the frictional horse power due to thinning of lubricant. So the volumetric efficiency drop is to be compensated by turbocharging to improve the thermal efficiency of insulated engine. Hence the present experimental work is planned accordingly. In the turbocharger the exhaust gases are expended in a turbine which is further coupled to engine. Further the turbine forces more air, proportionately more fuel into the combustion chamber, thereby enhancing the power output without increasing the cylinder capacity. Experiments are carried out in a single cylinder water cooled DI diesel engine with an air gap insulated piston, air-gap insulated liner and ceramic coated cylinder head and valves (Insulated engine) and the reduction in the volumetric efficiency is compensated with turbocharging. The insulated diesel engine with turbocharging gave the better performance and reduced smoke. Further the engine performance is also studied with the raise of intake boost pressure.